An “approximate knowledge”: event transmission in the post-9/11 informational culture (Altre Modernità, 2011)
The aim of the essay is to look back at 9/11 from the temporal perspective of 2011 and interpret it as a singularity, that is a moment of destabilization that hit the media sphere, accelerating an already existing shift in communication politics towards affective involvement. The dimension of pathic engagement that the televised images of 9/11 inspired, their becoming a source of collective emotional instability (i.e. a global “culture of fear”), has amplified preexisting modes of communication that relied on the energetic and mobilizing lure of audiovisual transmission. Rather than approaching 9/11 as a metaphysical occurrence, an absolute ‘event’ unencumbered by the territorializing pull of its own geopolitical genealogy, the essay engages with it as a phase boundary whose transformative impact can be sensed in the tactics of mobilization that inform contemporary communication practices.